Pro Crystal Enterprise/Business Objects XI programming - Ganz, Carl. (The expert's voice in .NET)
Pro Crystal Enterprise/BusinessObjects XI Programming shows you how to create customized solutions using the Business Objects/Crystal Enterprise object model. Here youll see the object model utilized to create professional-quality tools like on-demand web services, report metadata extraction, scheduling, security, and user management. Author Carl Ganz explains in detail how to build advanced reporting solutions for Crystal Enterprise/Business Objects XI. He shows how to integrate CE/BO XI with .NET 2.0 and Visual Studio to create more flexible, tailored, and responsive reporting solutions than have previously been possible. In short, you'll surpass what you thought you could achieve, and learn to create almost any imaginable reporting solution that Business Objects XI can handle. Welcome to BusinessObjects XI -- BusinessObjects XI server architecture -- Administration tools -- Using the central management console -- BusinessObjects XI SDK programming I -- BusinessObjects XI SDK programming II -- Crystal Reports and BusinessObjects XI -- Programming the report application server -- Enterprise solutions using the BusinessObjects XI SDK -- Security -- BusinessObjects unified Web services SDK -- Third-party solutions.